2020
DOI: 10.1097/aog.0000000000003637
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy Route and Numbers Reported by Graduating Residents in Obstetrics and Gynecology Training Programs

Abstract: OBJECTIVE: To characterize trends in self-reported numbers and routes of hysterectomy for obstetrics and gynecology residents using the Accreditation Council for Graduate Medical Education (ACGME) case log database. METHODS: Hysterectomy case log data for obstetrics and gynecology residents completing training between 2002–2003 and 2017–2018 were abstracted from the ACGME database. Total numbers of hysterectomies and modes of approach (abdominal, laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Hysterectomy is the most common surgical procedure in the domain of gynecology, and there are several surgical approaches to hysterectomy: abdominal hysterectomy (AH), vaginal hysterectomy (VH), laparoscopic hysterectomy (LH) with multi-port or single-port, robotic-assisted hysterectomy, and the emerging vNOTES hysterectomy [ 3 , 7 ]. Several randomized trials and meta-analyses had shown that the minimally invasive approach (VH or LH) was clearly superior to AH in terms of perioperative outcomes and recovery time [ 8 , 9 ], and recommend VH as a feasible procedure for the patients with benign indication and the LH as an alternative approach with the increased risk of urinary tract injury [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy is the most common surgical procedure in the domain of gynecology, and there are several surgical approaches to hysterectomy: abdominal hysterectomy (AH), vaginal hysterectomy (VH), laparoscopic hysterectomy (LH) with multi-port or single-port, robotic-assisted hysterectomy, and the emerging vNOTES hysterectomy [ 3 , 7 ]. Several randomized trials and meta-analyses had shown that the minimally invasive approach (VH or LH) was clearly superior to AH in terms of perioperative outcomes and recovery time [ 8 , 9 ], and recommend VH as a feasible procedure for the patients with benign indication and the LH as an alternative approach with the increased risk of urinary tract injury [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy is the most common surgical procedure in the domain of gynecology, and there are several surgical approaches to hysterectomy: abdominal hysterectomy (AH), vaginal hysterectomy (VH), laparoscopic hysterectomy (LH) with multi-port or single-port, robotic-assisted hysterectomy, and the emerging vNOTES hysterectomy [2,6]. Several randomized trials and meta-analyses have shown that the minimally invasive approach (VH or LH) is clearly superior to AH in terms of perioperative outcomes and recovery time [7,8], and recommend VH as a feasible procedure for the patients with benign indication and the LH as an alternative approach with the increased risk of urinary tract injury [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy is the most common surgical procedure in the domain of gynecology, and there are several surgical approaches to hysterectomy: abdominal hysterectomy (AH), vaginal hysterectomy (VH), laparoscopic hysterectomy (LH) with multi-port or single-port, robotic-assisted hysterectomy, and the emerging vNOTES hysterectomy [3,7]. Several randomized trials and meta-analyses had shown that the minimally invasive approach (VH or LH) was clearly superior to AH in terms of perioperative outcomes and recovery time [8,9], and recommend VH as a feasible procedure for the patients with benign…”
Section: Discussionmentioning
confidence: 99%